Hidden in the litter: cryptic diversity of the leaf-litter toad Rhinella castaneotica–proboscidea complex revealed through integrative taxonomy, with description of a new species from south-western Amazonia. Issue 1 (31st December 2022) - Ferrão, Miquéias; de Souza, Romildo Augusto; Colatreli, Olavo Pinhatti; Hanken, James; Lima, Albertina Pimentel
Abstract : Recent studies have showed that several species of frogs previously thought to be widespread throughout Amazonia are species complexes with each individual species displaying smaller geographic ranges and that only a small fraction of Amazonian frogs are indeed widely distributed. Evaluating cryptic diversity within these complexes and describing associated candidate species are crucial for biological conservation, especially in regions where tropical forest is rapidly vanishing such as in southern Amazonia. In this study, we integrate mitochondrial (16S rRNA), morphological, bioacoustic and breeding behaviour data to investigate whether populations of the leaf-litter toad Rhinella castaneotica – proboscidea complex are conspecific as suggested by former studies. Our molecular analysis recovered five main clades in this complex whose geographic distributions are likely limited by geographic barriers. Morphological, bioacoustic and breeding behaviour data support the heterospecificity of three of them. The names R. proboscidea sensu stricto and R. castaneotica sensu stricto are applied to the populations from central and eastern Amazonia, respectively. The population from south-western Amazonia is described herein as a new species. It differs from other members of the R. margaritifera species group by its snout–vent length (35.7–45.2 mm in males and 38.3–52.1 mm in females), poorly developed supratympanic crests, dorsal skin smooth in males and granular in females, and advertisement call with average call duration of 285 ± 28 ms, 11 ± 1 notes, last note duration of 41 ± 10 ms and dominant frequency of 1, 810 ± 220 Hz. Moreover, males of the new species vocalize while aggregated in temporary ponds unconnected to streams and do not exhibit necrophilic behaviour. South-western Amazonia is one of the Amazonian regions most threatened by forest loss and the formal description of new species adds impetus to support conservation strategies. http://zoobank.org/urn:lsid:zoobank.org:act:8F14DC28-DD0C-498C-B27D-113264EBE7CE2F0A